Thermally conductive spacer and thermally conductive composition

CN123023482APending Publication Date: 2026-10-30DENKA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580023759.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-27
Filing Date
2025-03-19
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

为了冷却,使用了金属制的散热器、壳体,但在使发热性电子部件与散热器等直接接触的情况下,在其界面处,空气微观地存在,有时成为导热的障碍

Benefits of technology

根据本发明,可提供即使反复暴露于高温及低温也能够维持高的导热性的导热性间隔体及导热性组合物。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123023482A_ABST
    Figure CN123023482A_ABST
Patent Text Reader

Abstract

The present disclosure provides a thermally conductive spacer or the like capable of maintaining high thermal conductivity even upon repeated exposure to high and low temperatures. The present disclosure provides a thermally conductive spacer comprising a thermosetting resin and a thermally conductive filler, a loss tangent tanδ at 25°C in a temperature increase process of the 3rd cycle when a cycle of increasing the temperature from -20°C to 150°C at a temperature increase rate of 5°C / min and decreasing the temperature from 150°C to -20°C at a temperature decrease rate of -5°C / min is repeated three times up a loss tangent tanδ at 25°C in a temperature decrease process of the 3rd cycle down is 2.0 or less. up / tanδ down is 2.0 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to thermally conductive spacers and thermally conductive compositions. Background Technology

[0002] With the miniaturization and high-output of heat-generating electronic components such as the CPU (Central Processing Unit) in personal computers, the heat generated per unit area by these components has become extremely large. This heat is even about 20 times that emitted by an iron. To prevent these heat-generating electronic components from malfunctioning over a long period, they need to be cooled. Metal heat sinks and housings are used for cooling, but when the heat-generating electronic components are in direct contact with the heat sinks, the presence of microscopic air at the interface sometimes becomes an obstacle to heat conduction. Therefore, to achieve efficient heat transfer, thermally conductive materials are sometimes used to separate the heat-generating electronic components and the heat sinks.

[0003] As thermally conductive materials, there are the following: thermally conductive spacers obtained by filling thermally conductive fillers into thermosetting resins and molding them into sheets; thermally conductive greases that can be coated and thin-filmed by filling thermally conductive fillers into fluid resins, etc.

[0004] To date, thermally conductive spacers that improve flexibility in addition to thermal conductivity have been developed (see Patent Document 1), etc.

[0005] Existing technical documents Patent documents Patent Document 1: International Publication No. 2023 / 162928 Summary of the Invention

[0006] The problem that the invention aims to solve Thermally conductive spacers can be used to place between a heat-generating element and a heat-dissipating element. In cases where the heat-generating element is a heat-generating electronic component such as the CPU (Central Processing Unit) of a personal computer, the thermally conductive spacer will be repeatedly exposed to high and low temperatures.

[0007] Therefore, the object of the present invention is to provide a thermally conductive spacer and a thermally conductive composition that can maintain high thermal conductivity even when repeatedly exposed to high and low temperatures.

[0008] Methods for solving problems In order to achieve the above objectives, the inventors of this application conducted in-depth research and found that a thermally conductive spacer with low hysteresis loss (tanδ) when repeatedly exposed to high and low temperatures can solve the above problems, thus completing the present invention.

[0009] That is, this disclosure includes the following implementation methods. [1] Thermally conductive spacer, comprising thermosetting resin and thermally conductive filler. When the cycle of heating from -20℃ to 150℃ at a rate of 5℃ / min and then cooling from 150℃ to -20℃ at a rate of -5℃ / min is repeated three times (where the first cycle is assumed to start from room temperature), the loss tangent tanδ at 25℃ during the heating process in the third cycle is... up The loss tangent tanδ at 25℃ during the cooling process down The ratio of tanδ up / tanδ down It is below 2.0. [2] As described in [1], the thermally conductive spacer, wherein the maximum value of the loss tangent during the aforementioned heating process and cooling process in the aforementioned third cycle is tanδ. max The value ranges from 0.10 to 1.0. [3] Thermally conductive spacers as described in [1] or [2], wherein the thermal conductivity is greater than 2.5 W / m·K as determined by ASTM D5470. [4] The thermally conductive spacer as described in any one of [1] to [3], wherein the increase rate of thermal resistance is less than 10% when the cycle of heating from -40°C to 150°C within 5 minutes and holding for 30 minutes, and cooling from 150°C to -40°C within 5 minutes and holding for 30 minutes is repeated for 500 hours. [5] The thermally conductive spacer as described in any one of [1] to [4], wherein the aforementioned thermosetting resin comprises addition-curing organosilicon. [6] The thermally conductive spacer as described in any one of [1] to [5] has an ASKER C hardness of 1 to 35. [7] A thermally conductive composition used to manufacture a thermally conductive spacer as described in any one of [1] to [6].

[0017] Invention Effects According to the present invention, a thermally conductive spacer and a thermally conductive composition can be provided that maintain high thermal conductivity even when repeatedly exposed to high and low temperatures. Attached Figure Description

[0018] [ Figure 1 This is a schematic diagram showing the relationship between the loss angle tangent tanδ and temperature T. Detailed Implementation

[0019] Hereinafter, embodiments of the present invention (hereinafter referred to as "this embodiment") will be described in detail. However, the present invention is not limited to the following embodiments, and various modifications can be made without departing from its spirit.

[0020] 1. Thermally conductive spacer The thermally conductive spacer of this embodiment comprises a thermosetting resin and a thermally conductive filler. When the temperature is increased from -20°C to 150°C at a rate of 5°C / min and then decreased from 150°C to -20°C at a rate of -5°C / min, repeated three times (wherein the first cycle is assumed to start from room temperature), the loss tangent tanδ at 25°C during the heating process of the third cycle... up The loss tangent tanδ at 25℃ during the cooling process down The ratio of tanδ up / tanδ down It is below 2.0.

[0021] The inventors of this application have discovered that even thermally conductive spacers with high initial thermal conductivity sometimes experience a decrease in thermal conductivity over time. Furthermore, further research revealed that this decrease in thermal conductivity is particularly significant when used in contact with a heating element that is intermittently and repeatedly heated. As the heating element changes in volume with temperature, the compressive force exerted on the thermally conductive spacer by the heating element fluctuates intermittently when the heating element is intermittently and repeatedly heated. Since the thermally conductive spacer cannot keep up with the volume changes associated with the temperature changes of the heating element, it is believed that excessive compression of the thermally conductive spacer or the formation of gaps may lead to a decrease in thermal conductivity at the interface.

[0022] Therefore, in order to provide a thermally conductive spacer that maintains high thermal conductivity even when repeatedly exposed to high and low temperatures, it is considered sufficient that the thermally conductive spacer can change shape to follow the volume change associated with the temperature change of the heating element. In the case of the thermally conductive spacer of this embodiment, by reducing the hysteresis loss during the high-temperature and low-temperature cycle (hereinafter also simply referred to as "thermal cycle"), it is ensured that the volume change associated with the temperature change of the heating element is followed. More specifically, this is achieved by reducing the loss tangent tanδ at 25°C during the heating process in a specified thermal cycle. up The loss tangent tanδ at 25℃ during the cooling process down The ratio of tanδ up / tanδ down It is specified within a certain range to ensure that the volume change accompanying the temperature change of the heating element can be tracked.

[0023] use Figure 1 Let me explain in more detail. Figure 1A schematic diagram illustrating the relationship between the loss tangent (tanδ) and temperature while measuring the loss tangent (tanδ) of a thermally conductive spacer during thermal cycling is provided. Figure 1 In the example shown, the loss tangent tanδ during the cooling process has a lower value compared to the loss tangent tanδ during the heating process, and the area enclosed by curve C corresponds to the hysteresis loss. With a large hysteresis loss, the thermally conductive spacer struggles to keep up with the volume change accompanying the temperature change of the heating element; consequently, the thermal conductivity of the spacer is considered to be reduced. It should be noted that... Figure 1 There are also cases where the loss tangent tanδ during the cooling process is higher than that during the heating process.

[0024] Regarding the thermally conductive spacer of this embodiment, the loss tangent tanδ during the heating process is 25°C. up The loss tangent tanδ at 25℃ during the cooling process down The ratio of tanδ up / tanδ down The conditions for achieving low hysteresis loss are specified. Thus, by achieving low hysteresis loss in the thermally conductive spacer, it is possible to follow the volume changes associated with temperature variations in the heating element, maintaining high thermal conductivity even under repeated exposure to high and low temperatures. Hereinafter, the characteristic of maintaining high thermal conductivity even under repeated exposure to high and low temperatures will be referred to as the "reliability" of the thermally conductive spacer.

[0025] 1.1. Physical properties of thermally conductive spacers 1.1.1. Loss tangent In this embodiment, the above ratio tanδ is used. up / tanδ down To describe low hysteresis loss. Specifically, when the cycle of heating from -20°C to 150°C at a rate of 5°C / min and then cooling from 150°C to -20°C at a rate of -5°C / min is repeated three times (where the first cycle is assumed to start from room temperature), the loss tangent tanδ at 25°C during the heating process in the third cycle is... up The loss tangent tanδ at 25℃ during the cooling process down The ratio of tanδ up / tanδ down It is below 2.0.

[0026] As described above, by making the above ratio tanδ up / tanδ down Below 2.0, low hysteresis losses can be reliably achieved, and the decrease in thermal conductivity caused by thermal cycling can be reliably suppressed. The above ratio is greater than tanδ. up / tanδ down For example, below 2.0 or above 0.5.

[0027] Therefore, regarding the above ratio tanδ up / tanδ down Preferably, the values ​​are 1.8 or less, 1.5 or less, 1.3 or less, 1.2 or less, and 1.1 or less. The above ratios are tanδ... up / tanδ down The lower limit value is not specifically defined, and is greater than tanδ. up / tanδ down For example, it can be 0.5 or higher, 0.6 or higher, 0.7 or higher, 0.8 or higher, or 0.9 or higher.

[0028] The loss tangent tanδ at 25℃ during the cooling process described above down The value of tanδ is not particularly limited, but preferably it is 0.10–1.0, 0.15–0.80, 0.20–0.70, or 0.22–0.60. Within the above ranges, tanδ down The value can be set to 0.25 or higher, 0.27 or higher, 0.30 or higher, 0.32 or higher, 0.35 or higher, 0.40 or higher, or 0.50 or higher, or it can be set to less than 0.55, less than 0.50, less than 0.45, less than 0.40, less than 0.35, less than 0.30, or less than 0.25.

[0029] The loss tangent tanδ at 25℃ during the above heating process up The value of tanδ is not particularly limited, but preferably it is 0.10–1.2, 0.15–1.0, 0.20–0.90, or 0.22–0.80. Within the above ranges, tanδ up The value can be set to 0.25 or higher, 0.27 or higher, 0.30 or higher, 0.35 or higher, 0.40 or higher, 0.50 or higher, or 0.60 or higher, or it can be set to below 0.70, below 0.65, below 0.60, below 0.50, below 0.40, below 0.35, or below 0.30.

[0030] Loss tangent tanδ up With tanδ down The difference (tanδ) up -tanδ down There are no particular limitations, but it is preferred to be -0.10 to 0.50, -0.05 to 0.30, -0.01 to 0.10, or 0.00 to 0.08.

[0031] By making the loss tangent tanδ up and tanδdown The values ​​of these values, as well as their ratios and differences, are all within the aforementioned ranges, thus tending to achieve lower hysteresis losses more reliably and further improve the reliability of thermally conductive spacers.

[0032] In this embodiment, the maximum value of the loss tangent tanδ during the heating and cooling processes of the third cycle is... max Preferably, the tangent is 0.10–1.0, 0.15–0.80, 0.15–0.80, 0.20–0.70, or 0.30–0.65. Within the above ranges, the maximum value of the loss tangent is tanδ. max The value can be set to 0.35 or higher, 0.40 or higher, 0.50 or higher, or 0.60 or higher, or it can be set to less than 0.60, less than 0.55, less than 0.50, less than 0.45, or less than 0.40. The maximum value of the loss tangent is tanδ. max Within the aforementioned range, there is a tendency for the repulsive force of the thermally conductive spacer to be within an appropriate range, thus mitigating the physical impact on the heat-generating and heat-dissipating elements.

[0033] The thermal cycle begins at room temperature, is raised to 150°C, and then cooled to -20°C. This cycle of raising the temperature from -20°C to 150°C and then cooling it back to -20°C is repeated. In this embodiment, to ensure a constant thermal history applied to the thermally conductive spacer and to evaluate thermal behavior under stable conditions, the loss tangent during the heating and cooling processes of the third cycle is used. Furthermore, from the viewpoint of more appropriately evaluating low hysteresis losses, the loss tangent at approximately the midpoint between -20°C and 150°C, i.e., 25°C, is used.

[0034] Furthermore, the loss tangent was measured using a rheometer under a compression condition of 15% from the initial thickness of the thermally conductive spacer, with a strain of 0.5% and a frequency of 1.0 Hz. More specifically, the loss tangent was measured using the method described in the examples. In the loss tangent measurement, the thermally conductive spacers can be appropriately stacked such that the initial thickness of the thermally conductive spacers is 2.0 mm or more.

[0035] To make the loss tangent tanδ up and tanδ down The values, ratios, and differences between them are within the aforementioned range. For example, the composition and manufacturing method of the thermally conductive spacer can be adjusted. For instance, the type of thermosetting resin can be changed, or the aging temperature and time after curing of the thermosetting resin can be adjusted in the manufacturing method of the thermally conductive spacer described later.

[0036] 1.1.2. ASKER C hardness A thermally conductive spacer can be disposed between a heat-generating element and a heat-dissipating element in a compressed manner. Therefore, from the viewpoint of mitigating physical impact on the heat-generating element and the heat-dissipating element, it is preferable that the flexibility, or in other words, the hardness, of the thermally conductive spacer is within a certain range.

[0037] Therefore, regarding the ASKER C hardness of the thermally conductive spacer, it is preferred to be 1 to 35, 3 to 20, or 5 to 15.

[0038] The ASKER C hardness of the thermally conductive spacer can be measured using an ASKER C type spring hardness tester according to SRIS0101 at 25°C, or more specifically, using the method described in the examples.

[0039] To ensure that the hardness of ASKER C is within the aforementioned range, the composition of the thermally conductive spacer can be adjusted, for example, by changing the type of thermosetting resin or adjusting the content of the thermally conductive filler.

[0040] 1.1.3. Thermal conductivity The thermally conductive spacer of this embodiment can be suitably used as a thermally conductive heat dissipation material. Therefore, the thermal conductivity of the thermally conductive spacer is preferably high. Specifically, regarding the thermal conductivity measured according to ASTM D5470, it is preferably 2.5 W / m·K or higher, 3.0 W / m·K or higher, 3.5 W / m·K or higher, 4.0 W / m·K or higher, or 5.0 W / m·K or higher. There is no particular upper limit to the thermal conductivity measured according to ASTM D5470, and the thermal conductivity can be, for example, 10 W / m·K or lower, 8.0 W / m·K or lower, or 7.0 W / m·K or lower.

[0041] The thermal conductivity of the thermally conductive spacer was determined according to ASTM D5470 under 30% compression, or more specifically, using the methods described in the examples.

[0042] To keep the thermal conductivity within the above range, one can adjust the type and content of the thermally conductive filler, for example.

[0043] The thermally conductive spacer of this embodiment maintains high thermal conductivity even when repeatedly exposed to high and low temperatures. Therefore, when a cycle is repeated for 500 hours, involving heating from -40°C to 150°C within 5 minutes and holding for 30 minutes, followed by cooling from 150°C to -40°C within 5 minutes and holding for 30 minutes, the increase rate of thermal resistance is preferably 10% or less, 9% or less, 8% or less, or 6% or less. There is no particular limitation on the lower limit of the increase rate of thermal resistance; for example, the increase rate can be 0% or more, 1% or more, or 3% or more.

[0044] Regarding the thermal resistance value of the thermally conductive spacer, it can be measured by placing the thermally conductive spacer in a measuring fixture with a smooth copper surface and allowing it to stand for 1 day. More specifically, it can be measured using the method described in the examples. The rate of increase in thermal resistance value can be calculated by measuring the thermal resistance value of the thermally conductive spacer before the above-mentioned cycle and then measuring the thermal resistance value of the thermally conductive spacer after the above-mentioned cycle.

[0045] 1.2. Composition of thermally conductive spacers The thermally conductive spacer of this embodiment comprises a thermosetting resin and a thermally conductive filler, and may include surfactants, curing catalysts, or other components as needed. The thermally conductive spacer preferably comprises thermosetting resin in a cured state, but uncured thermosetting resin may also remain.

[0046] 1.2.1. Thermosetting resins There are no particular limitations on the thermosetting resin; examples include silicone resins, epoxy resins, acrylic resins, urethane resins, and phenolic resins. Among these, silicone resins are preferred from the viewpoint of improving heat resistance and flexibility. A single thermosetting resin may be used, or two or more may be used in combination.

[0047] The thermosetting resin preferably comprises an addition-curing silicone resin that is cured by an addition reaction. There are no particular limitations on the addition-curing silicone resin; examples include polyorganosiloxanes having an alkenyl group and polyorganosiloxanes having a silyl group. The alkenyl group in the polyorganosiloxane is preferably vinyl. The thermally conductive spacer may comprise a commercially available thermosetting silicone resin and / or its cured form.

[0048] From the viewpoint of improving the thermal conductivity of the thermally conductive spacer, the thermosetting resin particularly preferably contains a vinyl-modified organopolysiloxane A having a vinyl group and a hydrosilyl-modified organopolysiloxane B having a hydrosilyl group. In the thermally conductive spacer, the vinyl-modified organopolysiloxane A and the hydrosilyl-modified organopolysiloxane B are preferably contained in a cross-linked state (i.e., cured) by an addition reaction, but unreacted vinyl-modified organopolysiloxane A and / or hydrosilyl-modified organopolysiloxane B may also be contained.

[0049] 1.2.1.1. Vinyl-modified organopolysiloxane A Vinyl-modified organopolysiloxane A (hereinafter also simply referred to as "organopolysiloxane A") is an organopolysiloxane having at least one vinyl group. Organopolysiloxane A may have vinyl groups in its side chains and / or at its ends. Such organopolysiloxanes have structural units represented by formula (a-1) or terminal structures represented by formula (a-2). Organopolysiloxane A may, for example, have: at least one of the structural units represented by formula (a-1) and the terminal structures represented by formula (a-2); and structural units represented by formula (a-3).

[0050] [Chemical Formula 1] Here, in formulas (a-1), (a-2), and (a-3), R is any monovalent hydrocarbon group that may have substituents. There are no particular limitations on such monovalent hydrocarbon groups; examples include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, and dodecyl; cycloalkyl groups such as cyclopentyl and cyclohexyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; aralkyl groups such as benzyl, 2-phenylethyl, and 2-phenylpropyl; and groups having substituents among these groups. Examples of substituents for the aforementioned monovalent hydrocarbon groups include halogen atoms, particularly fluorine or chlorine atoms.

[0051] Organopolysiloxane A can be used alone or in combination of two or more. There is no particular upper limit to the number of vinyl groups in organopolysiloxane A; for example, the average number of vinyl groups per molecule can be 1.0 to 4.0, or 2.0 to 3.0. The average number of vinyl groups per molecule of organopolysiloxane A can be 2.0.

[0052] The average vinyl number per molecule of organopolysiloxane A can be determined by NMR. Specifically, for example, using an ECP-300 NMR precipitator manufactured by JEOL, organopolysiloxane A is dissolved in deuterated chloroform as a deuterated solvent for determination. The average vinyl number per molecule can be calculated by dividing the result obtained in this manner by the average molecular weight of organopolysiloxane A.

[0053] The organopolysiloxane A preferably comprises organopolysiloxanes having vinyl groups at both ends. By using such organopolysiloxanes, the crosslinking density can be adjusted. As a result, there is a tendency to reduce the hysteresis loss of the thermally conductive spacer and further improve the reliability of the thermally conductive spacer.

[0054] The preferred weight-average molecular weight of the vinyl-modified organopolysiloxane A is 1,000–100,000, 1,500–75,000, or 2,500–50,000. In this specification, the weight-average molecular weight of each component can be determined by GPC (gel permeation chromatography).

[0055] In addition, the vinyl equivalent of the vinyl-modified organopolysiloxane A is preferably 0.1 to 1.0 mol / kg, 0.15 to 0.8 mol / kg, or 0.2 to 0.6 mol / kg.

[0056] The content of organopolysiloxane A is preferably 60 to 99.5% by weight or 80 to 95.0% by weight relative to the total content of components other than thermally conductive filler D. By keeping the content of vinyl-modified organopolysiloxane A within the above range, there is a tendency to reduce the hysteresis loss of the thermally conductive spacer and further improve the reliability of the thermally conductive spacer.

[0057] 1.2.1.2. Hydrosilyl-modified organopolysiloxane B Hydrosilyl-modified organopolysiloxane B (hereinafter also simply referred to as "organopolysiloxane B") is an organopolysiloxane having at least two hydrosilyl groups. Organopolysiloxane B may have hydrosilyl groups in its side chains and / or at its ends. Such organopolysiloxanes have structural units represented by formula (b-1) or terminal structures represented by formula (b-2). Organopolysiloxane B may, for example, have at least one of the structural units represented by formula (b-1) and the terminal structures represented by formula (b-2); and a structural unit represented by formula (b-3).

[0058] [Chemical Formula 2] Here, in formulas (b-1), (b-2), and (b-3), R is any monovalent hydrocarbon group that may have substituents. That is, in organopolysiloxane B, any monovalent hydrocarbon group that may have substituents is bonded to the side chain of the siloxane backbone. Examples of such monovalent hydrocarbon groups include groups that are the same as those that may be present in vinyl-modified organopolysiloxane A.

[0059] Organopolysiloxane B can be used alone or in combination of two or more. For example, organopolysiloxane B preferably includes at least one silane-modified organopolysiloxane B with a silane-alkyl side chain. x It may contain silyl-modified organopolysiloxanes with silyl groups at both ends.

[0060] Organopolysiloxane B x The side chains of the organopolysiloxane backbone have at least two hydrogen atoms, which, together with silicon atoms, form a hydrosilyl group. Organopolysiloxane B x It is possible to further have silane groups at both ends of the organopolysiloxane backbone, but it is preferable that there are no silane groups at both ends. In this case, organopolysiloxane B xPreferably, each of the two ends has three alkyl groups. Examples of such alkyl groups include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, etc., with methyl being the most preferred.

[0061] The number of silane alkyl groups in organopolysiloxane B is preferably more than 2.0, more than 2.5, or more than 3.0 per molecule on average. It should be noted that there is no particular upper limit on the number of silane alkyl groups in organopolysiloxane B. For example, the number of silane alkyl groups can be less than 8.0, less than 6.0, or less than 5.0 per molecule on average.

[0062] The average number of silane groups per molecule of organopolysiloxane B can be determined by NMR. Specifically, for example, using a JEOL ECP-300 NMR precipitator, organopolysiloxane B is dissolved in deuterated chloroform as a deuterated solvent for determination. The average number of silane groups per molecule can be calculated by dividing the result obtained in this manner by the average molecular weight of organopolysiloxane B.

[0063] The weight-average molecular weight of the silyl-modified organopolysiloxane B is preferably 100–10000, 150–7500, or 250–5000. Furthermore, the silyl equivalent of the silyl-modified organopolysiloxane B is preferably 1.0–10 mol / kg, 1.2–8.0 mol / kg, or 1.5–6.0 mol / kg.

[0064] The content of organopolysiloxane B, relative to the total amount of components other than thermally conductive filler D, is preferably 0.5–30% by weight, 1.0–20% by weight, 3.0–15% by weight, or 5.0–10% by weight. By keeping the content of organopolysiloxane B within the above range, there is a tendency to reduce the hysteresis loss of the thermally conductive spacer and further improve the reliability of the thermally conductive spacer.

[0065] 1.2.2. Surfactant C Surfactant C can be a component that improves the wettability of thermally conductive filler D to thermosetting resin. From the viewpoint of further improving the wettability of thermally conductive filler, the surfactant preferably contains at least one of anionic groups, cationic groups, and groups having a siloxane skeleton.

[0066] There are no particular limitations on the anionic group; for example, carboxyl, phosphate, phenolic hydroxyl, and sulfonic acid groups can be included. Preferably, the anionic group is selected from one or more groups consisting of carboxyl, phosphate, and phenolic hydroxyl, with carboxyl being the most preferred.

[0067] There are no particular limitations on the cationic group; examples include primary amino, secondary amino, tertiary amino, and quaternary ammonium cationic groups. Among them, the anionic group is preferably a tertiary amino group.

[0068] There are no particular limitations on the groups having a siloxane backbone; for example, groups formed from an organopolysiloxane backbone can be cited. Among them, groups having a siloxane backbone are preferably groups formed from a polydimethylsiloxane backbone.

[0069] The weight-average molecular weight of surfactant C is, for example, 20,000–150,000, 30,000–120,000, or 40,000–100,000. By keeping the weight-average molecular weight of the surfactant within the above range, there is a tendency to further improve the dispersibility of the thermally conductive filler D.

[0070] Surfactant C may be a component that improves the wettability of thermally conductive filler D to vinyl-modified organopolysiloxane A and / or hydrosilyl-modified organopolysiloxane B. From the viewpoint of further improving the wettability of the thermally conductive filler, the surfactant is preferably a copolymer containing at least two of the following: anionic groups, cationic groups, and groups having a siloxane backbone.

[0071] There are no particular limitations on the anionic group; examples include carboxyl, phosphate, phenolic hydroxyl, and sulfonic acid groups. Preferably, the anionic group is selected from one or more groups consisting of carboxyl, phosphate, and phenolic hydroxyl groups, with carboxyl being the most preferred.

[0072] There are no particular limitations on the cationic group; examples include primary amino, secondary amino, tertiary amino, and quaternary ammonium cationic groups. Among them, the anionic group is preferably a tertiary amino group.

[0073] There are no particular limitations on the group having a siloxane backbone; for example, groups formed from an organopolysiloxane backbone can be cited. Preferably, the group having a siloxane backbone is formed from a polydimethylsiloxane backbone. Examples of organopolysiloxane backbones include dialkylpolysiloxanes, diphenylpolysiloxanes, and alkylphenylpolysiloxanes. There are no particular limitations on the alkyl group comprising the siloxane backbone; for example, methyl, ethyl, propyl, butyl, pentyl, and hexyl can be cited. There are no particular limitations on the phenyl group comprising the siloxane backbone; for example, phenyl and benzyl can be cited.

[0074] Surfactant C is, for example, a copolymer containing: a (meth)acrylic monomer unit α (monomer unit α) having a carboxyl group, a (meth)acrylic monomer unit β (monomer unit β) having a tertiary amino group, and a (meth)acrylic monomer unit γ (monomer unit γ) having a siloxane backbone. When using such a copolymer, there is a tendency to further improve the dispersibility of the thermally conductive filler D and to further reduce the viscosity of the first and second agents. It should be noted that "monomer" refers to a monomer with polymerizable unsaturated bonds before polymerization, and "monomer unit" refers to a repeating unit that constitutes part of the copolymer after polymerization, meaning a unit derived from a specified monomer. Furthermore, regarding (meth)acrylic acid-, it includes acrylic acid- and methacrylic acid-, and the (meth)acrylic monomers include (meth)acrylates and (meth)acrylamide.

[0075] In the aforementioned copolymer, monomer units α, β, and γ can be randomly or block-formed. Preferably, at least monomer units α and γ are included as a random copolymer in the surfactant. By including monomer units α and γ in the form of a random copolymer, there is a tendency for the viscosity of the first agent to be further reduced.

[0076] There are no particular limitations on the monomer unit α; examples include acrylic acid, methacrylic acid, 2-acryloyloxyethyl succinic acid, and 2-methacryloyloxyethyl succinic acid. Among these, acrylic acid and 2-methacryloyloxyethyl succinic acid are preferred, and acrylic acid is more preferred. Monomer unit α can be used alone or in combination with two or more.

[0077] Relative to a total of 100 parts by weight of monomer unit α, monomer unit β, and monomer unit γ, the content of monomer unit α is, for example, 0.05 to 20 parts by weight, preferably 0.08 to 6.0 parts by weight, 0.1 to 5.0 parts by weight, 0.3 to 4.0 parts by weight, or 0.5 to 3.0 parts by weight. The content of monomer unit α within the above range can be 0.7 parts by weight or more, or 2.0 parts by weight or less.

[0078] There are no particular limitations on the monomer unit β; examples include dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, and 1,2,2,6,6-pentamethyl-4-piperidinyl methacrylate. Among these, dimethylaminoethyl methacrylate and 1,2,2,6,6-pentamethyl-4-piperidinyl methacrylate are preferred, and 1,2,2,6,6-pentamethyl-4-piperidinyl methacrylate is more preferred. The monomer unit β can be used alone or in combination with two or more.

[0079] Relative to a total of 100 parts by weight of monomer unit α, monomer unit β, and monomer unit γ, the content of monomer unit β is, for example, 0.02 to 4.0 parts by weight, preferably 0.05 to 4.0 parts by weight, 0.07 to 3.0 parts by weight, 0.8 to 2.0 parts by weight, or 0.1 to 1.0 parts by weight. Within the above ranges, the content of monomer unit β can be 0.3 parts by weight or more, or 0.8 parts by weight or less.

[0080] The number-average molecular weight of the monomer unit γ is preferably 1,500 to 50,000, more preferably 3,000 to 30,000, and even more preferably 4,000 to 20,000.

[0081] Relative to a total of 100 parts by weight of monomer unit α, monomer unit β, and monomer unit γ, the content of monomer unit γ is, for example, 70.0 to 99.9 parts by weight, preferably 80.0 to 99.5 parts by weight, 90.0 to 99.0 parts by weight, 93.0 to 98.8 parts by weight, or 96.0 to 98.7 parts by weight.

[0082] The content of surfactant C, relative to the total amount of components other than thermally conductive filler D, is preferably 0.5–30% by weight, 1.0–20% by weight, 1.5–15% by weight, or 2.0–10% by weight. By keeping the content of surfactant C within the above range, there is a tendency to further improve the dispersibility of thermally conductive filler D.

[0083] 1.2.3. Thermally conductive filler D Thermally conductive filler D is a filler with thermal conductivity. The thermal conductivity of thermally conductive filler D is not particularly limited, but for example, it can be 10 W / m·K or higher. There are no particular limitations on such thermally conductive filler D; examples include alumina (hereinafter also called "alumina"), aluminum nitride, silicon dioxide (especially crystalline silicon dioxide), boron nitride, silicon nitride, silicon oxide, zinc oxide, aluminum hydroxide, metallic aluminum, magnesium oxide, diamond, carbon, indium, gallium, copper, silver, iron, nickel, gold, tin, and metallic silicon.

[0084] The thermally conductive filler D preferably comprises one or more selected from the group consisting of boron nitride, aluminum nitride, alumina, silicon nitride, silicon oxide, magnesium oxide, metallic aluminum, and zinc oxide; more preferably, it comprises one or more selected from the group consisting of alumina, magnesium oxide, aluminum nitride, and metallic aluminum; and even more preferably, it comprises alumina. This is because the aforementioned thermally conductive fillers have high thermal conductivity, high insulation properties, and are inexpensive. The thermally conductive filler D can be used alone or in combination with two or more types.

[0085] The average particle size of the thermally conductive filler D is preferably 0.05 to 120 μm, more preferably 0.1 to 100 μm. By keeping the average particle size of the thermally conductive filler D within the above range, there is a tendency to further improve the dispersibility and filling properties of the thermally conductive filler D.

[0086] Furthermore, the thermally conductive filler D can be used by mixing fillers with different average particle sizes. As the thermally conductive filler D, it is preferable to use two or more of the following: thermally conductive fillers with an average particle size of 30 to 100 μm (D-1), thermally conductive fillers with an average particle size of 10 to 25 μm (D-2), thermally conductive fillers with an average particle size of 1.2 to 8.0 μm (D-3), and thermally conductive fillers with an average particle size of 0.05 to 1.0 μm (D-4). More preferably, it is preferable to use three or more, or all of them.

[0087] It should be noted that the average particle size of the thermally conductive filler can be measured, for example, using the Shimadzu SALD-20 laser diffraction particle size distribution measuring device (trade name). The evaluation sample is prepared, for example, as follows: 50 ml of pure water and 5 g of the thermally conductive filler powder to be measured are added to a glass beaker, stirred with a spatula, and then dispersed using an ultrasonic cleaner for 10 minutes. Afterward, using a dropper, the dispersed thermally conductive filler powder solution is added dropwise to the sampling section of the device, and the absorbance is measured after stabilization. In the laser diffraction particle size distribution measuring device, the particle size distribution is calculated based on the intensity distribution data of the diffracted / scattered light generated by the particles detected by the sensor. The average particle size is obtained by multiplying the measured particle size value by the relative particle amount (difference %) and dividing by the total relative particle amount (100%). It should be noted that the average particle size is the average diameter of the particles and can be calculated as the cumulative weight average value D50 (median particle size).

[0088] In this case, the content of thermally conductive filler (D-1) is preferably 30 to 70% by weight or 40 to 60% by weight relative to the total amount of thermally conductive filler D.

[0089] The content of thermally conductive filler (D-2) is preferably 0-30% by weight, 5-30% by weight, or 10-20% by weight relative to the total amount of thermally conductive filler D.

[0090] The content of thermally conductive filler (D-3) is preferably 5 to 30% by weight or 10 to 20% by weight relative to the total amount of thermally conductive filler D.

[0091] The content of thermally conductive filler (D-4) is preferably 0-30% by weight, 5-30% by weight, or 8-15% by weight relative to the total amount of thermally conductive filler D.

[0092] By using the thermally conductive filler D described above, there is a tendency to further improve the dispersibility and filling properties of the thermally conductive filler D.

[0093] Relative to 100 parts by weight of components other than thermally conductive filler D, the preferred content of thermally conductive filler D is 300–2500 parts by weight, 400–2000 parts by weight, or 500–1800 parts by weight. By keeping the content of thermally conductive filler D within the above ranges, there is a tendency to further improve the thermal conductivity of the thermally conductive spacer and reduce hysteresis losses. As a result, there is a tendency to further improve the reliability of the thermally conductive spacer.

[0094] 1.2.4. Solidified catalyst E The curing catalyst E is not particularly limited as long as it catalyzes the curing reaction of the thermosetting resin. When the thermosetting resin comprises vinyl-modified organopolysiloxane A and hydrosilyl-modified organopolysiloxane B, any catalyst capable of catalyzing the addition reaction of both is acceptable. Examples of such curing catalysts E include platinum compound catalysts, rhodium compound catalysts, and palladium compound catalysts. Among these, a platinum compound catalyst is preferred.

[0095] There are no particular limitations on the platinum compound catalyst; examples include elemental platinum, platinum compounds, and platinum-supported inorganic powders. There are also no particular limitations on the platinum compound; examples include chloroplatinic acid, platinum-olefin complexes, platinum-alcohol complexes, and platinum coordination compounds. Furthermore, there are no particular limitations on the platinum-supported inorganic powder; examples include platinum-supported alumina powder, platinum-supported silica powder, and platinum-supported carbon powder. The solidified catalyst E can be used alone or in combination with two or more types.

[0096] The preferred content of the curing catalyst E is 0.05 to 10 parts by weight, 0.1 to 5.0 parts by weight, or 0.3 to 3.0 parts by weight, relative to the content of 100 parts by weight of components other than the thermally conductive filler D.

[0097] 1.2.5. Other ingredients In addition to the above-mentioned components, thermally conductive spacers may also contain additives such as curing delay agents, colorants, silane coupling agents, and viscosity modifiers, depending on the requirements.

[0098] As a curing retarder, there are no particular limitations as long as it is a component that delays the curing reaction of the thermosetting resin. For example, if the thermosetting resin contains vinyl-modified organopolysiloxane A and hydrosilyl-modified organopolysiloxane B, an alkenyl alcohol such as 1-ethynyl-1-cyclohexanol can be cited as a curing retarder. If the thermally conductive spacer contains a curing retarder, the content of the curing retarder is preferably 0.001 to 1.0 parts by weight, more preferably 0.01 to 0.1 parts by weight, relative to 100 parts by weight of the content of components other than the thermally conductive filler D.

[0099] Examples of silane coupling agents include epoxy silane coupling agents such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and 3-glycidoxypropylmethyldimethoxysilane, (meth)acrylic acid modified silane coupling agents such as 3-methacryloyloxypropylmethyldimethoxysilane and 3-methacryloyloxytrimethoxysilane, and amino silane coupling agents such as N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane.

[0100] Examples of viscosity modifiers include, for instance, polysiloxanes other than vinyl-modified organopolysiloxane A and hydrosilyl-modified organopolysiloxane B, synthetic rubber latex, urethane resins, hydroxyethyl cellulose, carboxymethyl cellulose, methyl cellulose, polyvinyl alcohol, oxidized polyethylene, dibenzyl sorbitol, etc.

[0101] When the thermally conductive spacer contains additives such as colorants, silane coupling agents, and viscosity modifiers, the content of the additives is, for example, 0.001 to 0.2 parts by weight relative to 100 parts by weight of the content of the components other than the thermally conductive filler D.

[0102] 2. Applications The thermally conductive spacer of this embodiment can be suitably used as a thermally conductive and heat-dissipating material disposed between a heat-generating element and a heat-dissipating element. The heat-generating element is, for example, an electronic component, and the heat-dissipating element is, for example, a heat sink.

[0103] As an electronic component, there are no particular limitations; examples include heat-generating electronic components such as motors, battery packs, circuit boards in vehicle power systems, power transistors, and microprocessors. Similarly, as a heat sink, there are no particular limitations; examples include housings, especially metal housings.

[0104] 3. Manufacturing method The thermally conductive spacer of this embodiment can be manufactured by curing a thermally conductive composition comprising a thermosetting resin and a thermally conductive filler. The thermally conductive spacer of this embodiment may include, for example, a step of mixing the components to obtain a thermally conductive composition (hereinafter referred to as a "mixing step"); a step of coating the thermally conductive composition onto a substrate (hereinafter referred to as a "coating step"); and a step of curing the thermally conductive composition coated onto the substrate (hereinafter referred to as a "curing step").

[0105] In the mixing process, the components, including the thermosetting resin and the thermally conductive filler, are mixed. For example, a roller mill, kneader, Banbury mixer, or inline mixer can be used for mixing. More specifically, methods such as using a universal mixer, a mixing-type mixer, a Trimix (manufactured by Inoue Corporation), or a static mixer can be employed. In the mixing process, for example, the aforementioned components A to E are mixed with optional additives.

[0106] In the coating process, the thermally conductive composition obtained in the mixing process is coated onto a substrate and then formed. The preferred coating method is blade coating, but extrusion, pressing, or calendering can also be used depending on the viscosity of the composition. Examples of substrates include metal sheets and resin films such as PET films. It is preferable to coat the substrate with a thickness of 0.3–10 mm or 0.5–5.0 mm for the thermally conductive spacer.

[0107] In the curing process, the thermally conductive composition coated on the substrate is cured to form a thermally conductive spacer. The curing conditions can be adjusted according to the type of thermosetting resin and the type of curing catalyst. For example, the curing process can be a process of heating at 100 to 170°C for 5 to 60 minutes.

[0108] After the curing process described above, the cured thermally conductive composition can be directly used as a thermally conductive spacer. However, the manufacturing method of this embodiment preferably further includes an aging process at a predetermined temperature after the curing process (hereinafter referred to as the "aging process"). By including the aging process, there is a tendency to stabilize the physical properties of the thermally conductive spacer. As a result, there is a tendency to further reduce hysteresis loss and further improve the reliability of the thermally conductive spacer.

[0109] Regarding the aging temperature in the aging process, it is preferable to be -10 to 20°C, -5 to 15°C, or 0 to 10°C. Furthermore, regarding the aging time, it is preferable to be 5 to 80 hours, 10 to 50 hours, 12 to 48 hours, or 20 to 36 hours. Aging can be carried out in the atmosphere or in inert gases such as nitrogen or argon. By aging under these conditions, there is a tendency to further reduce hysteresis losses and further improve the reliability of the thermally conductive spacer.

[0110] 4. Thermally conductive composition The thermally conductive composition of this embodiment is a composition used to manufacture the thermally conductive spacer of this embodiment. As detailed in section 3. Manufacturing Method above, the thermally conductive composition of this embodiment can be used to manufacture a thermally conductive spacer by molding and curing.

[0111] The thermally conductive composition of this embodiment may contain components A to E in the amounts described above. The thermally conductive composition may also contain additives such as curing delay agents in the amounts described above.

[0112] Example The present invention will be described in more detail below through embodiments, but the present invention is not limited to the following embodiments.

[0113] 1. Manufacturing of thermally conductive spacers Based on the proportions (parts by weight) listed in Table 1, the following ingredients were mixed. The mixing of each ingredient was performed using a mixing machine ARE-310 (manufactured by Thinky Corporation, trade name).

[0114] Vinyl-modified organopolysiloxanes RH-Vi100E (manufactured by Runhe Chemical Industry, trade name), a two-terminated vinyl-modified organopolysiloxane, with an average number of vinyl groups per molecule of 2, a vinyl equivalent of 0.39 mol / kg, and a weight-average molecular weight of 11,000. Hydrogen-silyl-modified organopolysiloxanes RH-Vi100E (manufactured by Runhe Chemical Industry, trade name), a two-terminal trimethylsilyl side-chain hydroxysilyl modified organopolysiloxane, with an average number of hydroxysilyl groups per molecule of 3 or more, a hydroxysilyl equivalent of 1.8 mol / kg, and a weight-average molecular weight of 3000–4000. Surfactants Surfactants manufactured using the method described later • Curing catalyst Platinum complex polymethylvinylsiloxane solution (manufactured by Bluestar Silicones, trade name: Siliconease Catalyst 12070) • Curing delay agent PA90 (manufactured by Elkem, trade name), a mixture of 1-ethynyl-1-cyclohexanol, polyorganosiloxane, and filler (1-ethynyl-1-cyclohexanol concentration 10% by mass). Thermally conductive fillers Denka Corporation, spherical alumina, average particle size: 90 μm, thermal conductivity 35 W / m·K DAW45S (manufactured by Denka, trade name), spherical alumina, average particle size: 45μm, thermal conductivity 35W / m·K Denka Corporation, spherical alumina, average particle size: 20 μm, thermal conductivity 35 W / m·K DAW05 (manufactured by Denka, trade name), spherical alumina, average particle size: 5μm, thermal conductivity 35W / m·K AA-05 (manufactured by Sumitomo Chemical Co., Ltd., trade name), crystalline alumina, average particle size: 0.5 μm, thermal conductivity 35 W / m·K • 2-Liquid Addition Curing Type Organosilicon SE1885 (manufactured by Toray Dow Corning Co., Ltd., trade name) (Agent A and Agent B) contains vinyl-modified organopolysiloxanes and hydrosilyl-modified organopolysiloxanes. Next, the mixed composition was coated onto a PET film using a doctor blade. The coating amount was adjusted so that the thickness of the cured thermally conductive spacer was 1.0 mm. Then, the composition was cured at 150°C for 30 minutes. In Example 4 and Comparative Example 2, the cured product obtained in the curing process was used as the thermally conductive spacer.

[0115] In Examples 1 and 2, the cured material obtained in the curing process was then further aged at 5°C for 24 hours under atmospheric conditions to obtain a thermally conductive spacer.

[0116] It should be noted that, as a comparative example 1, a commercially available thermally conductive spacer (manufactured by Honeywell, TGP8000) was used.

[0117] The surfactant was synthesized as follows. First, acrylic acid (manufactured by Toa Synthetic Co., Ltd.): 1.5 parts by weight, 1,2,2,6,6-pentamethyl-4-piperidinyl methacrylate (manufactured by ADEKA Co., Ltd., “ADK STAB LA-82”): 0.5 parts by weight, and α-butyl-ω-(3-methacryloyloxypropyl)polydimethylsiloxane (manufactured by JNC Co., Ltd., “Silaplane FM-0725”, number average molecular weight 10000): 98.0 parts by weight were added to an autoclave equipped with a stirrer. Next, a mixed solution of azobisisobutyronitrile (manufactured by Tokyo Chemical Co., Ltd.) as an initiator (0.05 parts by weight relative to 100 parts by weight of the total (meth)acrylic acid monomers), and toluene (reagent grade) and isopropanol (reagent grade) as solvents in a volume ratio of 7:3 was added, and the autoclave was purged with nitrogen. Then, the autoclave was heated in an oil bath at 65°C for 20 hours to carry out free radical polymerization. After polymerization, the mixture was degassed at 120°C under reduced pressure for 1 hour to obtain the surfactant.

[0118] The polymerization rate relative to 100% monomer input was analyzed by gas chromatography, and the result was over 98%. This suggests that the ratio of monomer units in the surfactant is similar to the monomer input ratio.

[0119] In addition, the weight-average molecular weight of the obtained surfactant was determined using GPC (gel permeation chromatography) in the form of weight-average molecular weight converted to standard polystyrene, and the result was 85,000. It should be noted that the determination conditions are as follows.

[0120] High-efficiency GPC unit: Tosoh Corporation "HLC-8020" Columns: 1 Tosoh "TSK guardcolumn MP (×L)" 6.0mm ID×4.0cm column and 2 Tosoh "TSK-GELMULTIPOREHXL-M" 7.8mm ID×30.0cm columns (theoretical plate count is 16,000), totaling 3 columns (theoretical plate count is 32,000 as a whole). Developing solvent: Tetrahydrofuran Detector: RI (Differential Refractometer) 2. Physical property determination and evaluation (Determination of loss tangent) Two 1.0 mm thick thermally conductive spacers were stacked and placed in a rheometer (Thermo Fisher Scientific, "MARS40"). Corresponding to the flat shape of the rheometer, the thermally conductive spacers were made into Φ35 mm circles. Dynamic viscoelasticity measurements were continuously performed while undergoing thermal cycling under conditions of 0.5% strain and 1 Hz, with a 15% compression from the initial thickness (2.0 mm). The thermal cycling started at room temperature and repeated the following cycle: heating to 150 °C, then cooling to -20 °C, then heating from -20 °C to 150 °C, and then cooling from 150 °C to -20 °C. The heating rate was set to 5 °C / min, and the cooling rate was set to -5 °C / min. The thermal cycle was repeated 7 times.

[0121] The loss tangent tanδ at 25℃ during the third heating cycle up The loss tangent tanδ at 25℃ during the cooling process down and their ratio tanδ up / tanδ down And the maximum value of the loss tangent tanδ during the heating and cooling processes of the third cycle. max As shown in Table 1.

[0122] (Determination of ASKER C hardness) The ASKER C hardness was measured at 25°C using an ASKER rubber hardness tester (Type C) manufactured by Polymer Instruments Co., Ltd., according to SRIS0101. Specifically, the thermally conductive spacer was cut into 2cm squares using a cutting blade, and the ASKER C hardness (ASKER C hardness 1) of 12 sheets stacked together was measured. The results are shown in Table 1.

[0123] (Evaluation of thermal conductivity) Thermally conductive spacers, cut into 10mm x 10mm pieces and 1mm thick, were used. Under 30% compression, the thermal resistance was measured according to ASTM D5470 using a resin material thermal resistance measuring device (manufactured by Hitachi Technology & Service Corporation). Thermal resistance values ​​were measured for spacers of multiple thicknesses (1mm, 2mm), and the thickness and thermal resistance values ​​were plotted. The thermal conductivity was calculated based on the slope at each point. The results are shown in Table 1.

[0124] A 1mm thermally conductive spacer, fabricated using the method described above, is placed on a measuring fixture with a smooth copper surface measuring 2cm wide and 4cm deep. Then, it is clamped with a fixture having a copper surface of the same size. Excess thermally conductive spacer is scraped off, and the mixture is adjusted to a width of 2cm, a depth of 4cm, and a thickness of 0.7mm. The screws are then tightened. After one day, a heater is installed on the upper surface of the fixture, and thermocouples are installed on both the upper and lower surfaces. The initial value of the thermal resistance is then measured.

[0125] For the testing fixture with solidified material, a thermal shock test was performed from -40°C to 150°C, and the thermal resistance value was measured again. The holding time at -40°C and 150°C was set to 30 minutes, and the temperature rise and fall from -40°C to 150°C and from 150°C to -40°C were set to within 5 minutes, for a total of 500 hours. The heater and thermocouple were installed in the same manner as for the initial value measurement, and the thermal resistance value after the thermal shock test was measured. The increase rate (%) of the thermal resistance value before and after the thermal cycle was calculated based on the thermal resistance value before the thermal cycle. The results are shown in Table 1. As shown in Table 1, the thermally conductive spacer of the embodiment maintains high thermal conductivity and high reliability even when repeatedly exposed to high and low temperatures.

[0126] [Table 1]

Claims

1. A thermally conductive spacer comprising a thermosetting resin and a thermally conductive filler. The cycle of heating from -20°C to 150°C at a rate of 5°C / min and then cooling from 150°C to -20°C at a rate of -5°C / min was repeated three times. In the first cycle (assuming the temperature rises from room temperature), the loss tangent tanδ at 25°C during the temperature rise process in the third cycle is... up The loss tangent tanδ at 25℃ during the cooling process down The ratio of tanδ up / tanδ down It is below 2.

0.

2. The thermally conductive spacer as described in claim 1, wherein, The maximum value of the loss tangent during the heating and cooling processes in the third cycle, tanδ. max It ranges from 0.10 to 1.

0.

3. The thermally conductive spacer as described in claim 1, wherein, The thermal conductivity is above 2.5 W / m·K, as measured by ASTM D5470.

4. The thermally conductive spacer as described in claim 1, wherein, When the cycle of heating from -40°C to 150°C within 5 minutes and holding for 30 minutes, and then cooling from 150°C to -40°C within 5 minutes and holding for 30 minutes is repeated for 500 hours, the increase in thermal resistance is less than 10%.

5. The thermally conductive spacer as claimed in claim 1, wherein, The thermosetting resin comprises addition-curing silicone.

6. The thermally conductive spacer as described in claim 1, wherein the ASKER C hardness is 1 to 35.

7. A thermally conductive composition used to manufacture a thermally conductive spacer according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Resin composition and semiconductor device

    WO2023162928A1